Operational semantics of a domain specific language for real time musician–computer interaction - Echeveste, José; Cont, Arshia; Giavitto, Jean-Louis; Jacquemard, Florent (Discrete event dynamic systems, 2013)
With the advent and availability of powerful personal computing, the computer music research and industry have been focusing on real-time musical interactions between musicians and computers; delegating human-like actions to computers who interact with a musical environment. One common use-case of this kind is Automatic Accompaniment where the system is comprised of a real-time machine listening system that in reaction to recognition of events in a score from a human performer, launches necessary actions for the accompaniment section. While the real-time detection of score events out of live musicians’ performance has been widely addressed in the literature, score accompaniment (or the reactive part of the process) has been rarely discussed. This paper deals with this missing component in the literature from a formal language perspective. We show how language considerations would enable better authoring of time and interaction during programming/composing and how it addresses critical aspects of a musical performance (such as errors) in real-time. We sketch the real-time features required by automatic musical accompaniment seen as a reactive system. We formalize the timing strategies for musical events taking into account the various temporal scales used in music. Various strategies for the handling of synchronization constraints and the handling of errors are presented. We give a formal semantics to model the possible behaviors of the system in terms of Parametric Timed Automata .